Parenting Style and Bullying Behavior of School Age Children at a State Elementary School - Sopaliu, Dily Rahmawati; Kariyadi; Widiyati, Wiwik (Omni Nursing Journal, 2024)
Background: Parenting styles are ways of attitude or behavior of parents when interacting with children, including how to apply rules, teach values/ norms, give attention and affection, and show good attitudes and behaviors so that they are used as role models for their children. Therefore, the habits and behaviors that parents carry out will be applied by children to their friends even though it is bad, which may have an impact on children to bully others because it is considered right. Objective: This study aimed to determine the relationship between parenting style and bullying behavior in school age children. Methods: This study used quantitative design with cross-sectional approach. Total sampling technique was used to select sample, which resulted in a total of 30 respondents. Results: Majority of respondents were 10 years old, accounting for 16 (53.3%) respondents and male accounting for 16 (53.3%) respondents. Most parenting style implemented by parents were authoritarian style, amounting 15 (50%) respondents and majority of respondents did not do bullying, accounting for 18 (60%) respondents. The Chi-square test obtained a p-value of 0.012 (p < 0.05), indicating that there was a relationship between parenting style and bullying behavior in school age children at one of state elementary schools in Maluku. Conclusion: There is a correlation between parenting style and bullying behaviour of school age children. It is expected that parents educate their children well and apply good parenting so that bullying behavior does not occur at school.